PENGARUH EMPLOYEE ENGAGEMENT DAN KOMITMEN KARYAWAN TERHADAP KINERJA KARYAWAN BANK GENERASI Y - Puspa, Deisya Monika; Sagala, Ella Jauvani (Fakultas Ekonomi dan Bisnis Universitas Katolik Indonesia Atma Jaya, 2018)
The purpose of this study was to determine the effect of employee engagement and commitment to the performance of generation y employees at BRI Bank in Wonosobo Regency. The population in this study were employees of Bank BRI Wonosobo which were categorized as Generation Y (ages 18-38 years). The method applied in this study is a quantitative method. Based on the results of the test and data analysis, employee engagement and employee commitment have a significant effect on employee performance. The results of this study are expected to provide input for BRI Bank in Wonosobo Regency.